2013
DOI: 10.1088/0004-637x/770/1/40
|View full text |Cite
|
Sign up to set email alerts
|

PRIMUS: INFRARED AND X-RAY AGN SELECTION TECHNIQUES AT 0.2 <z< 1.2

Abstract: We present a study of Spitzer /IRAC and X-ray active galactic nucleus (AGN) selection techniques in order to quantify the overlap, uniqueness, contamination, and completeness of each. We investigate how the overlap and possible contamination of the samples depends on the depth of both the IR and X-ray data. We use Spitzer /IRAC imaging, Chandra and XMM-Newton X-ray imaging, and spectroscopic redshifts from the PRism MUlti-object Survey (PRIMUS) to construct galaxy and AGN samples at 0.2 < z < 1.2 over 8 deg 2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
133
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(151 citation statements)
references
References 71 publications
17
133
1
Order By: Relevance
“…Using ∼250 ISCS/IDCS clusters from 0.5 < z < 2, we examine the fraction of AGNs as a function of clustercentric radius and redshift. We quantify AGN content by the contribution of AGN emission to the optical-to-MIR SED, a long wavelength baseline which allows us to select a broad range of AGN types (e.g., Hickox et al 2009;Mendez et al 2013;Chung et al 2014). We find that AGN-dominated and AGN-composite galaxies are found in excess of the fraction in the field in high redshift (z  1) clusters, indicating that the cluster environment is fueling AGNs through galaxy interactions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Using ∼250 ISCS/IDCS clusters from 0.5 < z < 2, we examine the fraction of AGNs as a function of clustercentric radius and redshift. We quantify AGN content by the contribution of AGN emission to the optical-to-MIR SED, a long wavelength baseline which allows us to select a broad range of AGN types (e.g., Hickox et al 2009;Mendez et al 2013;Chung et al 2014). We find that AGN-dominated and AGN-composite galaxies are found in excess of the fraction in the field in high redshift (z  1) clusters, indicating that the cluster environment is fueling AGNs through galaxy interactions.…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, we quantify the ratio of the UV-MIR luminosity from best-fit galaxy templates to the total UV-MIR luminosity (galaxy+AGN templates): F gal ≡ L gal /L total , with F gal = 0.5 providing a useful dividing line between sources whose luminosity is primarily from an AGN ( F gal < 0.5) versus those whose luminosity is primarily provided by the (host) galaxy ( F gal > 0.5). This technique takes advantage of a broad wavelength range, providing a more complete selection in terms of AGN type and the balance between AGN and host galaxy emission, than AGN indicators that use only limited wavelength windows or colors (e.g., Hickox et al 2009;Mendez et al 2013;Chung et al 2014). Checking against spectroscopic redshifts, Assef et al (2010) found that the ability of this SED fitting technique to measure F gal is relatively independent of the derived photometric redshift; even galaxies with large uncertainties in their photometric redshift have a small uncertainty in F gal .…”
Section: Photometric Redshiftsmentioning
confidence: 99%
“…Identifying AGNs based on infrared-only colors has the highest reliability at brighter fluxes (e.g., Barmby et al 2006;Cardamone et al 2008;Donley et al 2008Donley et al , 2012Eckart et al 2010;Mendez et al 2013). As we show in Figure 17 To answer this, we again plot the distribution of R W1 -for the different luminosity bins in Figure 18 and is an efficient and robust diagnostic to select unobscured and obscured AGNs, including Comptonthick AGNs that can be missed altogether by X-ray surveys, additional metrics, such as R W1 -, are useful in recovering a reddened population missed by this infrared-only cut (Stern et al 2012;Yan et al 2013;Donoso et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The GLIMPSE survey detected mid-IR emission (G022.4768−00.1539) at magnitudes 11.393± 0.047 (3.6 μm), 11.161±0.068 (4.5 μm), 11.056±0.090 (5.8 μm), and 10.779±0.092 (8.0 μm). Both the large mid-IR brightness and colors suggest that the IR source is not an AGN (Stern et al 2005;Mendez et al 2013).…”
Section: Ir Counterpart Of Xmmuj183245−0921539mentioning
confidence: 97%